Curator tours museum (Raton Range Raton, 1992)
Article is about a Curator from the Metropolitan Museum of Art in New York City touring the Raton Museum.
Newspaper article + Photograph of Donya Schimansky
Master list item #: 29
File location is in the Raton file Cabinet
Keywords: Schimansky, Donya -- Curator/Librarian; Metropolitan Museum of Art -- New York; Raton Museum; Raton Arts Council -- Sponsor; Museum Tours; Lectures; Discussions; "Influence of Pre-Columbian and Mexican Art and Architecture"; Raton, New Mexico